ANALISIS PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), RETURN ON ASSETS (ROA) TERHADAP PRICE TO BOOK VALUE (PBV), DENGAN DIVIDEND PAYOUT RATIO SEBAGAI VARIABEL INTERVENING - Annisa, Rizka; Chabachib, Mochammad (Diponegoro Journal of Management, 2017)
Price to book value is one of the variables used by investors to make investment decisions. Judging from the information value of book value per year and also the ratio of the previous year in the independent variable so that investors can determine the pace of further investment. This study aimed to analyze the influence of Current Ratio, Debt to Equity Ratio, Return on Assets to Price to Book Value by using the Dividend Payout Ratio as an intervening variable in the manufacturing industry sector companies listed on the Stock Exchange 2011-2014 period. This study uses 24 manufacturing companies listed in Indonesia Stock Exchange (BEI) during the period 2011-2014 as the sample. Determination of the samples was done by purposive sampling method. The analysis technique used is regression analysis and path analysis. Furthermore, Sobel test is used to test the strength in the interest of the indirect effect of independent variables on the dependent variable by an intervening variable. The results showed that CR has negative effect and not significant on PBV, while DER has significant positive effect on PBV. ROA has significant positiveÂ  effect on PBV and DPR has significant positive effect on the DER. Furthermore, Sobel test results show that DPR cannot mediate the effect of CR on PBV and also DPR cannot mediate the effect of DER on PBV while DPR can mediate the effect of ROA on PBV.